Helical tomotherapy of lymph node-negative early-stage breast cancer after breast-conserving surgery: long-term results - Zwicker, Felix; Klepper, Rudolf; Hauswald, Henrik; Hoefel, Sebastian; Raether, Luis; Huber, Peter E.; Debus, Jürgen; Schempp, Michael (Anticancer research, 2023)
Background/Aim: Adjuvant radiotherapy is an integral part of the interdisciplinary curative treatment of breast cancer. We aimed to examine the long-term clinical results of helical tomotherapy in female patients with local restricted, lymph node negative breast cancer after breast-conserving surgery. Patients and Methods: In this single-centre analysis, 219 female patients with early-stage breast cancer (T1/2) and no lymph node metastasis (N0) following breast-conserving surgery and sentinel-node biopsy were treated with adjuvant fractionated whole breast radiation therapy using helical tomotherapy. When boost irradiation was indicated, it was administered sequentially or using the simultaneous-integrated boost technique. Local control (LC), metastasis and survival rates, acute toxicity, late toxicity, and secondary malignancy rates were analysed retrospectively. Results: The mean follow-up time was 71 months. The 5- and 8-year overall survival (OS) rates were 97.7% and 92.1%, respectively. The 5- and 8-year LC rates were 99.5% and 98.2%, while the 5- and 8-year metastasis-free survival (MFS) rates of 97.4% and 94.3%, respectively. Patients with G3 grading or negative hormone receptor status did not show significantly different results. Acute erythema occurred in 79% (grade 0-2) and 21% (grade 3) of the patients. Lymphedema of the ipsilateral arm and pneumonitis occurred in 6.4% and 1.8% of the treated patients. None of the patients developed >grade 3 toxicities during follow-up, while 1.8% developed a secondary malignancy during follow-up. Conclusion: Helical tomotherapy showed excellent long-term results and low toxicity rates. The incidence rates of secondary malignancy were relatively low and correlated with pre-existing data on radiotherapy, suggesting wider implementation of helical tomotherapy in adjuvant radiotherapy for breast cancer patients.